“CONSUMER PRICES-EXPENDITURE-INCOME” CONNECTION: ITS MANIFISTATIONS AND DEVELOPMENT IN RA - Saribekyan, Amalya (Bulletin of Yerevan University G: Economics, 2019)
The issues concerning the socioeconomic condition of the country, its living standards, income and consumer prices of the population have recently been intensively discussed in Armenia. According to the official data of the Central Bank of Armenia, 12-month inflation, fluctuating around the average level of 2.5 % in 2018, made up 1.85 % in December. As the CBA points out, “Inflation in 2018 is lower than it was anticipated; however, it is definitely erroneous to say that a year lacks boost in prices.” The most important point here is not the fact of low inflation, but the real increase in the prices of goods of first priority, that leads to an increase in the cost of the consumer basket. Thus, it is noteworthy to say that while focusing more attention on the phenomenon of inflation, very little attention is paid to the issue of increasing the cost of food and consumer baskets. Under these conditions, the minimum salary does not overpower the cost of the minimum consumer basket, and the minimum pension payment cannot overpower even the cost of the food basket. Thus, the improvement of the social condition of the population must be sought in the context of the direct and inverse multi-factorial effects of the price-expenditure-income chain